Negative electrode, solid lithium-ion battery, and method for manufacturing a negative electrode
Patent Information
- Application Number
- JP2025059479
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166508000001 
Figure 2026166508000002
Abstract
Description
[Technical Field]
[0001] This invention relates to a negative electrode, a solid lithium-ion battery, and a method for manufacturing a negative electrode. [Background technology]
[0002] In recent years, research and development has been conducted on solid-state lithium-ion batteries that contribute to energy efficiency, in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy.
[0003] Patent Document 1 describes a negative electrode active material layer containing silicon active material particles and solid electrolyte particles. In this layer, the amount of oxygen atoms in the silicon active material particles is less than 5.0% by mass, and the average particle size of the solid electrolyte particles is 1.0 μm or less. Patent Document 1 also describes a solid-state secondary battery having a negative electrode active material layer. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2024-148560 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, the negative electrode active material layer described in Patent Document 1 may result in low dispersibility of silicon active material particles, which in turn reduces the discharge capacity of the solid-state secondary battery and increases its initial resistance.
[0006] The present invention aims to provide a negative electrode that can increase the discharge capacity of a solid lithium-ion battery and lower its initial resistance. [Means for solving the problem]
[0007] (1) A negative electrode comprising a negative electrode mixture layer containing a silicon-based active material and a solid electrolyte, wherein a 25 μm square region in a backscattered electron image at 5000× magnification of a cross section of the negative electrode mixture layer is, so that the area is uniform, subjected to X1 division, X2 division, ···, X n-1 division and X n division (provided that X1, X2, ···, X n-1 and X n are each a different integer of 2 or more), and the standard deviations σX1 [%], σX2 [%], ···, σX n-1 [%] and σX n [%] of the area ratio [%] occupied by the region attributed to the silicon-based active material in the ternarized region are determined, then the standard deviation σ [%] of σX1, σX2, ···, σX n-1 and σX n is determined, and the average value σ of the standard deviation σ ave [%] satisfies the formula 0.2<σ ave <2.0 .
[0008] (2) A 25 μm square region in a backscattered electron image at 5000× magnification of a cross section of the negative electrode mixture layer is, so that the area is uniform, subjected to X1 division, X2 division, ···, X n-1 division and X n division, and the average values SX of the area ratio [%] occupied by the region attributed to the silicon-based active material in the ternarized region 1,ave [%], SX 2,ave [%], ···, SX n-1,ave [%] and SX n,ave [%] are determined, then the average value S [%] of SX 1,ave , SX 2,ave , ···, SX n-1,ave and SX n,ave is determined, and the average value S of S ave [%] satisfies the formula 50≦S ave ≦80 . The negative electrode according to (1).
[0009] (3) A 25 μm square region in a backscattered electron image at 5000× magnification of a cross section of the negative electrode mixture layer is, so that the area is uniform, subjected to X1 division, X2 division, ···, Xn-1 Split and X n The region is divided, and the average value of the percentage [%] of the area occupied by the region attributed to the solid electrolyte within the trinarized region is calculated. 1,ave '[%], SX 2,ave '[%], ..., SX n-1,ave '[%] and SX n,ave After calculating [%], SX 1,ave ', SX 2,ave ',,,,SX n-1,ave 'and SX n,ave When we find the average value S'[%] of ', the average value of S' is S ave '[%] is an expression S ave +S ave <99.9 The negative electrode described in (2) that satisfies the following conditions.
[0010] (4) The negative electrode according to any one of (1) to (3), wherein the negative electrode composite layer has a silicon-based active material content of 50% by mass or more and 80% by mass or less.
[0011] (5) The solid electrolyte is the negative electrode according to any one of (1) to (4), having a median diameter of 100 nm or more and 1000 nm or less.
[0012] (6) The negative electrode according to any one of (1) to (5), wherein the negative electrode composite layer has a solid electrolyte content of 10% by mass or more and 50% by mass or less.
[0013] (7) The negative electrode according to any one of (1) to (6), wherein the negative electrode composite layer further comprises a binder.
[0014] (8) The negative electrode according to (7), wherein the negative electrode composite layer contains 0.5% by mass or more and 3% by mass or less of the binder.
[0015] (9) The negative electrode according to (7) or (8), wherein the binder is one or more selected from the group consisting of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and polyimide.
[0016] (10) The negative electrode according to any one of (1) to (9), wherein the solid electrolyte is a sulfide solid electrolyte.
[0017] (11) The negative electrode according to (10), wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
[0018] (12) The negative electrode according to any one of (1) to (11), wherein the negative electrode composite layer has a thickness of 10 μm or more and 100 μm or less.
[0019] (13) A solid lithium-ion battery comprising the negative electrode described in any one of (1) to (12).
[0020] A method for manufacturing a negative electrode according to any one of (1) to (12), comprising the step of applying a slurry containing the silicon-based active material, the solid electrolyte, and a solvent to form the negative electrode composite layer, wherein the solvent has a boiling point of 120°C or higher. [Effects of the Invention]
[0021] According to the present invention, it is possible to provide a negative electrode that can increase the discharge capacity of a solid lithium-ion battery and lower its initial resistance. [Modes for carrying out the invention]
[0022] Embodiments of the present invention will be described below.
[0023] [Negative electrode] The negative electrode of this embodiment comprises a negative electrode composite layer containing a silicon-based active material and a solid electrolyte. Here, a 25 μm square region of the backscattered electron image of the cross-section of the negative electrode composite layer, at 5000x magnification, is divided into X1, X2, ..., X n-1 Split and X n Division (however, X1, X2, ..., X n-1 and X nEach of these is a distinct integer of 2 or more.) In addition, the standard deviations of the percentage of the area [%] occupied by the region attributed to the silicon-based active material in the trinarized region are σX1[%], σX2[%], ..., σX n-1 [%] and σX n After calculating [%], σX1, σX2, ..., σX n-1 and σX n When you find the standard deviation σ[%], the mean σ of the standard deviation σ is... ave [%] is an expression 0.2 < σ ave <2.0 Satisfying the equation 1.7<σ ave <2.0 It is preferable that the following conditions be met. 0.2 < σ ave <2.0 To satisfy this condition, the dispersibility of the silicon-based active material and solid electrolyte increases, resulting in a higher discharge capacity and lower initial resistance of the solid lithium-ion battery. At this time, the trinarized region can be assigned to a region that does not contain the active material or solid electrolyte, or to the active material and solid electrolyte, based on the analysis results of an energy-dispersive X-ray fluorescence spectrometer (EDX). Here, X1, X2, ..., X n-1 and X n The combinations are not particularly limited, but examples include 4, 9, 16, and 25.
[0024] Furthermore, a 25 μm square region of the backscattered electron image of the cross-section of the negative electrode composite layer, magnified 5000 times, was divided into 4, 9, 16, and 25 sections so that the area would be uniform, and the average value of the percentage of the area attributed to the silicon-based active material within the trinarized region was calculated S4. ave [%], S9 ave [%], S16 ave [%] and S25 ave After calculating [%], S4 ave S9 ave S16 ave and S25 ave The mean S[%] of S is calculated as follows: ave [%] is an expression 50≦S ave ≤80 It is preferable that the following conditions be met: 55≦S ave ≤80 It is even more preferable that the following condition be met. 50≦S ave ≤80 When this condition is met, the dispersibility of silicon-based active materials and solid electrolytes increases.
[0025] At this time, a 25 μm square region of the backscattered electron image of the cross-section of the negative electrode composite layer, magnified 5000 times, is divided into 4, 9, 16, and 25 sections so that the area is uniform, and the average value of the percentage of the area occupied by the solid electrolyte within the trinarized region is calculated S4. ave '[%], S9 ave '[%], S16 ave '[%] and S25 ave After calculating the percentage, S4 ave ', S9 ave ', S16 ave 'and S25 ave When we find the average value S'[%] of ', the average value of S' is S ave '[%] is an expression S ave +S ave <99.9 It is preferable that the following conditions be met: S ave +S ave <98.0 It is more preferable to satisfy the following conditions: S ave +S ave <96.0 It is even more preferable that the following condition be met. S ave +S ave <99.9 When this condition is met, the dispersibility of silicon-based active materials and solid electrolytes increases.
[0026] The content of silicon-based active material in the negative electrode composite layer is preferably 50% by mass or more and 80% by mass or less, and more preferably 55% by mass or more and 78% by mass or less. When the content of silicon-based active material in the negative electrode composite layer is 50% by mass or more and 80% by mass or less, the dispersibility of the silicon-based active material and the solid electrolyte is improved.
[0027] The silicon-based active material is not particularly limited, but examples include elemental silicon, silicon alloys, silicon oxides, and composite materials containing silicon and other dissimilar elements. Examples of silicon alloys include SiC alloys, SiN alloys, SiTi alloys, SiAl alloys, SiLi alloys, and SiCu alloys. An example of a silicon oxide is SiO. Examples of composite materials containing silicon and other dissimilar elements include silicon-lithium composite materials, silicon-carbon composite materials, and silicon-aluminum composite materials. The composite material containing silicon and other dissimilar elements may or may not be a silicon alloy.
[0028] From the viewpoint of the dispersibility of the silicon-based active material and the solid electrolyte, the silicon-based active material 1 is preferably a composite material containing silicon and a different heterogeneous element.
[0029] The median diameter of the solid electrolyte is preferably 100 nm or more and 1000 nm or less, more preferably 100 nm or more and 800 nm or less, and even more preferably 200 nm or more and 700 nm or less. When the median diameter of the solid electrolyte is 100 nm or more, aggregation of the solid electrolyte is suppressed, resulting in a higher discharge capacity and lower initial resistance of the solid lithium-ion battery. On the other hand, when the median diameter of the solid electrolyte is 1000 nm or less, aggregation of the silicon-based active material is suppressed, resulting in a higher discharge capacity and lower initial resistance of the solid lithium-ion battery.
[0030] The solid electrolyte content in the negative electrode composite layer is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 40% by mass or less. When the solid electrolyte content in the negative electrode composite layer is 10% by mass or more and 50% by mass or less, the dispersibility of the silicon-based active material and the solid electrolyte is improved.
[0031] The solid electrolyte is not particularly limited as long as it can conduct lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of dispersibility of the silicon-based active material and the solid electrolyte, and argyrodite-type sulfide solid electrolytes are particularly preferred. Furthermore, sulfide solid electrolytes are preferred from the viewpoint of lithium ion conductivity, and argyrodite-type sulfide solid electrolytes are particularly preferred. When the lithium ion conductivity of the solid electrolyte is high, the lithium ion conduction resistance inside the negative electrode is lowered, and the discharge capacity is increased. In addition, even if the interface between the solid electrolyte and the silicon-based active material is reduced, if the lithium ion conductivity of the solid electrolyte is high, lithium ions can conduct, and the decrease in discharge capacity is suppressed even after repeated charging and discharging.
[0032] Sulfide solid electrolytes include, for example, a metal element (M) that acts as a conductive ion and sulfur (S). Examples of M include Li, Na, K, Mg, and Ca. Among these, Li is preferred.
[0033] The sulfide solid electrolyte preferably contains Li, A (one or more elements selected from the group consisting of P, Si, Ge, Al, and B), and S, and more preferably Li and P. Furthermore, the sulfide solid electrolyte may further contain halogen elements (e.g., Cl, Br, I) from the viewpoint of ionic conductivity. The sulfide solid electrolyte may also further contain O.
[0034] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are positive numbers, and Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga or In), Li v P w S x Cl y Br z (v, w, x, y, z>0) and the like. Among these, Li is preferable because the initial resistance decreases even after repeated charge and discharge v P w S x Cl y Br z (v, w, x, y, z>0) is preferred, and from the viewpoint of ionic conductivity, Li v P w S x Cl y Br z (0<v<10, 0<w<5, 0<x<5, 0<y<5, 0<z<5) is more preferable, and examples thereof include Li 5.4 PS 4.4 Cl 0.8 Br 0.8 and the like.
[0035] The description of, for example, "Li2S-P2S5" means a sulfide solid electrolyte obtained using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0036] Furthermore, the sulfide solid electrolyte may be sulfide glass or crystalline sulfide glass, or a crystalline material obtained by a solid-phase method. Sulfide glass can be obtained, for example, by performing a mechanical milling method (for example, a method of milling using a ball mill) on the raw material composition. Crystalline sulfide glass can be obtained, for example, by heat-treating sulfide glass at a temperature above its crystallization temperature.
[0037] The negative electrode composite layer preferably further contains a binder. This improves the dispersibility of the silicon-based active material and the solid electrolyte, and suppresses the decrease in discharge capacity after repeated charging and discharging of the solid lithium-ion battery.
[0038] The binder content in the negative electrode composite layer is preferably 0.5% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less. When the binder content in the negative electrode composite layer is 0.5% by mass or more and 3% by mass or less, the dispersibility of the silicon-based active material and the solid electrolyte is increased, and the decrease in discharge capacity after repeated charging and discharging of the solid lithium-ion battery is suppressed.
[0039] The binder is preferably one or more selected from the group consisting of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and polyimide. This improves the dispersibility of the silicon-based active material and solid electrolyte, and suppresses the decrease in discharge capacity after repeated charging and discharging of the solid lithium-ion battery.
[0040] The negative electrode composite layer may further contain a conductive additive. This improves the dispersibility of the silicon-based active material and solid electrolyte, and lowers the initial resistance of the solid lithium-ion battery. The conductive additive is not particularly limited, but examples include acetylene black, multiwalled carbon nanotubes (MCNTs), and single-walled carbon nanotubes (SCNTs). The content of the conductive additive in the negative electrode composite layer is not particularly limited, but for example, it is 0.05% by mass or more and 5% by mass or less.
[0041] The thickness of the negative electrode composite layer is preferably 10 μm or more and 100 μm or less, more preferably 15 μm or more and 80 μm or less, and even more preferably 15 μm or more and 50 μm or less. When the thickness of the negative electrode composite layer is 10 μm or more and 100 μm or less, the volume change of the negative electrode is further suppressed when the solid lithium-ion battery is repeatedly charged and discharged, and the decrease in discharge capacity after repeated charging and discharging of the solid lithium-ion battery is suppressed.
[0042] The method for forming the negative electrode composite layer is not particularly limited, but one example is a method of applying a slurry containing a silicon-based active material, a solid electrolyte, and a solvent. The boiling point of the solvent is preferably 120°C or higher, and more preferably 150°C or higher. When the boiling point of the solvent is 120°C or higher, rapid evaporation of the solvent is suppressed when the slurry is applied, so excessive aggregation of components in the slurry is suppressed, and as a result the dispersibility of the silicon-based active material and the solid electrolyte is improved. The boiling point of the solvent is, for example, 180°C or lower.
[0043] Solvents with a boiling point of 120°C or higher are not particularly limited, but examples include butyl butyrate (boiling point 166°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), and decane (boiling point 174°C). Among these, butyl butyrate is preferred from the viewpoint of dispersibility of silicon-based active materials and solid electrolytes.
[0044] The negative electrode of this embodiment, for example, has a negative electrode composite material layer formed on a negative electrode current collector, and is applied to solid lithium-ion batteries.
[0045] The materials that make up the negative electrode current collector are not particularly limited, but examples include silver, palladium, gold, platinum, aluminum, copper, nickel, stainless steel, and carbon. Among these, copper, stainless steel, and nickel are preferred from the viewpoint of conductivity and cost.
[0046] The shape of the negative electrode current collector is not particularly limited, but examples include foil-like, plate-like, mesh-like, non-woven fabric-like, and foam-like forms.
[0047] The thickness of the negative electrode current collector is not particularly limited, but for example, it is between 0.1 μm and 1 mm.
[0048] [Solid-state lithium-ion battery] The solid-state lithium-ion battery of this embodiment includes the negative electrode of this embodiment, but further comprises, for example, a positive electrode and an electrolyte. The electrolyte is not particularly limited, but examples include solid electrolytes and gel electrolytes. A fully solid-state lithium-ion battery comprising a solid electrolyte layer will be described below.
[0049] (solid electrolyte layer) The solid electrolyte constituting the solid electrolyte layer is not particularly limited, but examples include sulfide solid electrolytes and oxide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of the initial Coulomb efficiency of the solid lithium-ion battery of this embodiment, and argyrodite-type sulfide solid electrolytes are particularly preferred.
[0050] Furthermore, the sulfide solid electrolyte contained in the solid electrolyte layer is the same as the sulfide solid electrolyte contained in the negative electrode composite layer.
[0051] The form of the solid electrolyte is not particularly limited, but for example, particles can be used.
[0052] The solid electrolyte content in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more and 99% by mass or less.
[0053] The solid electrolyte layer may further contain a binder or the like.
[0054] The method for forming the solid electrolyte layer is not particularly limited, but one example is a method of applying a slurry containing a solid electrolyte and a solvent.
[0055] The thickness of the solid electrolyte layer is, for example, between 0.1 μm and 1000 μm.
[0056] (positive electrode) For example, the positive electrode has a positive electrode composite layer formed on the positive electrode current collector.
[0057] The positive electrode composite layer contains a positive electrode active material. The positive electrode active material is not particularly limited, but examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese (LiMn2O4), Li 1+x Mn 2-x-y M y Examples include O4(x+y=2) (where M is one or more elements selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn), lithium titanate, and LiMPO4 (where M is one or more elements selected from the group consisting of Fe, Mn, Co, and Ni).
[0058] The content of the positive electrode active material in the positive electrode composite layer is not particularly limited, but for example, it is 50% by mass or more and 99% by mass or less.
[0059] The positive electrode composite layer may further contain a solid electrolyte. The solid electrolyte is not particularly limited as long as it is capable of conducting lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes.
[0060] The positive electrode composite layer may further contain a binder, a conductive additive, and the like.
[0061] The method for forming the positive electrode composite layer is not particularly limited, but one example is a method of applying a slurry containing a positive electrode active material and a solvent.
[0062] The materials used to constitute the positive electrode current collector are not particularly limited, but examples include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium. Among these, aluminum, aluminum alloys, and stainless steel are preferred.
[0063] The shape of the positive electrode current collector is not particularly limited, but examples include foil-shaped and plate-shaped.
[0064] The thickness of the positive electrode composite layer is, for example, 0.1 μm to 1000 μm.
[0065] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and the above embodiments may be modified as appropriate within the scope of the spirit of the present invention. [Examples]
[0066] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0067] [Example 1] Solid electrolytes, slurries, negative electrodes, and half-cells were manufactured in a nitrogen-filled glove box as follows:
[0068] (Manufacturing of solid electrolytes) Li2S, P2S5, LiCl, and LiBr 5.4 PS 4.4 Cl 0.8 Br 0.8 After weighing to meet the required composition, the mixture was mixed in an agate mortar for 5 minutes. 2 g of the resulting mixture was placed in a container of a planetary ball mill, followed by the addition of dehydrated heptane and ZrO2 balls, and the container was completely sealed. The container was mounted in the planetary ball mill and mechanically milled at a disc rotation speed of 500 rpm for 20 hours. The mixture was then dried at 110°C for 1 hour to remove the heptane and obtain a coarse-grained material.
[0069] The coarse-grained material was granulated. Specifically, the coarse-grained material was mixed with dehydrated heptane and dibutyl ether, and adjusted to a total volume of 10 g and a solid content concentration of 10% by mass. The resulting mixture was placed in a container of a planetary ball mill, then ZrO2 balls were added, and the container was completely sealed. The container was mounted on the planetary ball mill, and mechanical milling was performed at a base plate rotation speed of 150 rpm. After that, it was dried, and the median diameter (D 50 ) 200 nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 ) was obtained.
[0070] (Slurry manufacturing) Using a rotation / revolution mixer, 70 parts by mass of silicon / carbon composite material and median diameter (D 50 ) 200 nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 28 parts by mass of ) were mixed. Next, 2 parts by mass of polyvinylidene fluoride (PVDF) and butyl butyrate were added, and the mixture was mixed using a rotation-revolution mixer. After mixing, the mixture was dispersed using an ultrasonic homogenizer to obtain a slurry. Here, butyl butyrate has a boiling point of 166°C.
[0071] (Manufacturing of negative electrodes) To obtain the negative electrode, a slurry was applied to a copper foil used as a negative electrode current collector, dried, and then press-molded at a pressure of 980 MPa to form a negative electrode composite layer with a thickness of 30.5 μm. At this time, it was dried at atmospheric pressure at 40°C for 20 minutes, then at atmospheric pressure at 80°C for 20 minutes, and then dried under reduced pressure at 110°C for 2 hours.
[0072] [Example 2] (In the production of solid electrolytes), the time of mechanical milling is changed, and the median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8A negative electrode was obtained in the same manner as in Example 1, except that a ) was obtained. At this time, the thickness of the negative electrode composite layer was 33.3 μm.
[0073] [Comparative Example 1] (In the production of solid electrolytes), the time of mechanical milling is changed, and the median diameter (D 50 ) 3000nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 A negative electrode was obtained in the same manner as in Example 1, except that ) was obtained. At this time, the thickness of the negative electrode composite layer was 30.8 μm.
[0074] [Mean value of standard deviation σ σ σ ave ] Using a scanning electron microscope (SEM), a 5000x magnification first backscattered electron image of the cross-section of the negative electrode composite layer was acquired under the conditions of an acceleration voltage of 5kV and a probe current of 1nA (see Figures 1-3). Next, a 25 μm square region A was arbitrarily selected, and then divided into n (n=4, 9, 16, 25) sections so that the area was equal, and designated as regions A1, A2, ..., and An. Next, the numerical contrast range of regions A1, A2, ..., and An (region A) was divided into three equal parts, i.e., regions A1, A2, ..., and An (region A) were trinarized. At this time, based on the analysis results of an energy-dispersive X-ray fluorescence analyzer (EDX) attached to the SEM, the trinarized regions were assigned, in order from the numerical contrast range with the highest contrast, to the region without active material or solid electrolyte, the active material, and the solid electrolyte. Next, for each region (A1, A2, ..., An), the percentage of the area occupied by the region assigned to the solid electrolyte (S1, S2, ..., Sn) was calculated, and then the standard deviation σn (n=4, 9, 16, 25) of S1, S2, ..., Sn was calculated. Then, the standard deviation σ of σ4, σ9, σ16, and σ25 was calculated.
[0075] In the second and third backscattered electron images as well, after performing the above operation, the mean value of the standard deviation σ is calculated. ave The result was calculated.
[0076] [Average value S of the area occupied by regions attributed to the active material] ave ] Using a scanning electron microscope (SEM), a 5000x magnification first backscattered electron image of the cross-section of the negative electrode composite layer was acquired under the conditions of an acceleration voltage of 5kV and a probe current of 1nA. Next, a 25μm square region A was arbitrarily selected, and then divided into n (n=4, 9, 16, 25) sections so that the area was equal, and designated as regions A1, A2, ..., and An. Next, the numerical contrast range of regions A1, A2, ..., An (region A) was divided into three equal parts, i.e., regions A1, A2, ..., An (region A) were trinarized. At this time, based on the analysis results of an energy-dispersive X-ray fluorescence analyzer (EDX) attached to the SEM, the trinarized regions were assigned, in order from the numerical contrast range with the highest contrast, to the region without active material or solid electrolyte, the active material, and the solid electrolyte. Next, in each region (A1, A2, ..., An), the percentage of the area occupied by the region attributed to the active material (S1, S2, ..., Sn) is calculated, and then the average value of S1, S2, ..., Sn is calculated. ave We calculated (n=4, 9, 16, 25). Next, S4 ave S9 ave S16 ave and S25 ave The average value S was calculated.
[0077] In the second and third backscattered electron images as well, after performing the above operation, the average value of S S ave The result was calculated.
[0078] [Average value S of the area occupied by regions assigned to solid electrolytes] ave '] Using a scanning electron microscope (SEM), a backscattered electron image (5000x magnification) of the cross-section of the negative electrode composite layer was acquired under the conditions of an acceleration voltage of 5kV and a probe current of 1nA. Next, a 25μm square region A was arbitrarily selected, and then divided into n (n=4, 9, 16, 25) sections so that the area was equal, and designated as regions A1, A2, ..., and An. Next, the numerical contrast range of regions A1, A2, ..., An (region A) was divided into three equal parts, i.e., regions A1, A2, ..., An (region A) were trinarized. At this time, based on the analysis results of an energy-dispersive X-ray fluorescence analyzer (EDX) attached to the SEM, the trinarized regions were assigned, in order from the numerical contrast range with the highest contrast, to the region without active material or solid electrolyte, the active material, and the solid electrolyte. Next, in each region (A1, A2, ..., An), the percentage of the area occupied by the region assigned to the solid electrolyte (S1', S2', ..., Sn') is calculated, and then the average value of S1', S2', ..., Sn' is calculated. ave We calculated (n=4, 9, 16, 25). Next, S4 ave ', S9 ave ', S16 ave 'and S25 ave The average value S was calculated.
[0079] In the second and third backscattered electron images as well, after performing the above operation, the average value of S' S ave ' was calculated.
[0080] Table 1 shows the σn, σ, Sn, S, Sn', and S' of the first backscattered electron image of Example 1.
[0081] [Table 1]
[0082] [Half-cell manufacturing] Sulfide solid electrolyte Li 5.4 PS 4.4 Cl 0.8 Br 0.8After placing the material into a cylindrical ZrO2 tube, it was pressed between stainless steel jigs to obtain a solid electrolyte pellet. Next, the solid electrolyte pellet and the negative electrode were stacked, and then molding pressure was applied to form a solid electrolyte layer. Then, a lithium foil was stacked on the solid electrolyte layer on the side opposite the negative electrode, and then it was restrained with a restraining pressure of 3 MPa to obtain a half-cell.
[0083] [Discharge capacity] Initial charge and discharge cycles were performed on a half-cell at a 1 / 3C rate, and the initial discharge capacity was measured. Next, 10 charge and discharge cycles were performed on the same half-cell at a 1 / 3C rate, and the discharge capacity was measured.
[0084] [Initial resistance] An initial resistance test was performed on a half-cell using a potentiostat SI1287 (Solartron Alytical) under the following measurement conditions. The impedances at multiple frequencies measured by the AC impedance method were plotted to obtain a Nyquist plot. Based on the Nyquist plot, the 0.1 Hz resistance, conduction resistance, reaction resistance, and diffusion resistance were determined. Temperature: 25℃ Applied AC voltage: 10mV Frequency: 0.1Hz~1MHz
[0085] Table 2 shows the evaluation results for the initial resistance and discharge capacity of half-cells.
[0086] [Table 2]
[0087] Table 1 shows that using the negative electrodes of Examples 1 and 2 results in low initial resistance (reaction resistance and diffusion resistance) and high discharge capacity of the half-cell. In contrast, the negative electrode of Comparative Example 1 has a σ of 2.36, resulting in high initial resistance (reaction resistance and diffusion resistance) of the half-cell and low discharge capacity.
[0088] Furthermore, it can be seen that using the negative electrodes of Examples 1 and 2 results in higher discharge capacity not only for the initial discharge capacity of the half-cell but also for the discharge capacity after 10 charge-discharge cycles compared to using the negative electrode of Comparative Example 1. The negative electrode of Comparative Example 1 has a σ of 2.36, which means that the dispersibility of the silicon-based active material is low and there is little interface between the silicon-based active material and the solid electrolyte, resulting in high initial resistance and low initial discharge capacity. Moreover, after 10 charge-discharge cycles of the half-cell, the silicon-based active material expands and contracts repeatedly, further reducing the interface between the silicon-based active material and the solid electrolyte, thus further decreasing the discharge capacity.
Claims
1. The negative electrode composite layer comprises a silicon-based active material and a solid electrolyte. A 25 μm square region in a backscattered electron image at 5000x magnification of the cross section of the negative electrode composite material layer is divided into X 1 divisions, X 2 divisions, ..., X n-1 divisions and X n divisions (provided that X 1 , X 2 , ..., X n-1 and X n are each 2 or more different integers), and the standard deviation σX of the area ratio [%] occupied by the region attributed to the silicon-based active material in the ternarized region 1 [%], σX 2 [%], ..., σX n-1 [%] and σX n [%] are determined, then the standard deviation σ [%] of σX 1 , σX 2 , ..., σX n-1 and σX n is determined, the average value σ of the standard deviation σ ave [%] is represented by the formula 0.2<s ave <2.0 A negative electrode that satisfies the following conditions.
2. A 25 μm square region of the backscattered electron image of the cross-section of the negative electrode composite layer, magnified 5000 times, is divided into X-shaped areas so that the area is uniform. 1 division, x 2 Division,...,X n-1 Division and X n The region is divided, and the average value of the percentage [%] of the area occupied by the region attributed to the silicon-based active material within the trinarized region is calculated. 1,ave [%], SX 2,ave [%],...,SX n-1,ave [%] and SX n,ave After calculating [%], SX 1,ave SX 2,ave , ..., SX n-1,ave and SX n,ave When we find the average value S [%], the average value of S is S ave [%] is the formula 50≦S ave ≦80 A negative electrode according to claim 1, satisfying the requirements.
3. A 25 μm square region of the backscattered electron image of the cross-section of the negative electrode composite layer, magnified 5000 times, is divided into X-shaped areas so that the area is uniform. 1 division, x 2 Division,...,X n-1 Division and X n The region is divided, and the average value of the percentage [%] of the area occupied by the region attributed to the solid electrolyte within the trinarized region is calculated. 1,ave '[%], SX 2,ave '[%],...,SX n-1,ave '[%] and SX n,ave After calculating the [%], SX 1,ave ', SX 2,ave ',,,SX n-1,ave 'and SX n,ave When we find the average value S'[%] of ', the average value of S' is S ave '[%] is in the formula S ave +S ave ’<99.9 The negative electrode according to claim 2, satisfying the requirements.
4. The negative electrode according to any one of claims 1 to 3, wherein the negative electrode composite layer contains 50% by mass or more and 80% by mass or less of the silicon-based active material.
5. The negative electrode according to any one of claims 1 to 3, wherein the solid electrolyte has a median diameter of 100 nm or more and 1000 nm or less.
6. The negative electrode according to any one of claims 1 to 3, wherein the negative electrode composite layer has a solid electrolyte content of 10% by mass or more and 50% by mass or less.
7. The negative electrode according to any one of claims 1 to 3, wherein the negative electrode composite layer further comprises a binder.
8. The negative electrode according to claim 7, wherein the negative electrode composite layer contains 0.5% by mass or more and 3% by mass or less of the binder.
9. The negative electrode according to claim 7, wherein the binder is one or more selected from the group consisting of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, acrylic resin, and polyimide.
10. The negative electrode according to any one of claims 1 to 3, wherein the solid electrolyte is a sulfide solid electrolyte.
11. The negative electrode according to claim 10, wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
12. The negative electrode according to any one of claims 1 to 3, wherein the negative electrode composite layer has a thickness of 10 μm or more and 100 μm or less.
13. A solid lithium-ion battery comprising the negative electrode described in any one of claims 1 to 3.
14. A method for manufacturing a negative electrode according to any one of claims 1 to 3, The process includes applying a slurry containing the silicon-based active material, the solid electrolyte, and the solvent to form the negative electrode composite layer. The solvent is a solvent with a boiling point of 120°C or higher, a method for manufacturing a negative electrode.
Citation Information
Patent Citations
Negative electrode active material layer and solid secondary battery
JP2024148560A